2014
DOI: 10.1371/journal.pone.0091080
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol Is a Favorable Prognostic Factor and Negatively Correlated with C-Reactive Protein Level in Non-Small Cell Lung Carcinoma

Abstract: BackgroundAlthough the alterations of lipid profile in lung cancer have been documented, the prognostic value of serum HDL-C level and its correlation with inflammation in NSCLC remain unknown.Subjects and MethodsLevels of preoperative serum lipid concentrations (including HDL-C, LDL-C, TC, and TG) and the inflammatory biomarker C-reactive protein level (CRP) were retrospectively analyzed in 228 patients with NSCLC and in 300 healthy controls. The serum lipid levels in these two populations were compared. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 44 publications
4
72
1
Order By: Relevance
“…In consistent with our results on cancer prognosis, a prospective cohort study including 30 179 male and 26 005 female participants who were followed up for 9 years presented that low serum cholesterol was associated with increased risk for overall cancer mortality (HR = 1.52; 95% CI: 1.06–2.18) . Previous epidemiological studies also provided that decreased level of HDL‐C could be an easily measured predictor for inferior prognosis in breast, prostate cancer and non‐small cell lung carcinoma . Wang et al .…”
Section: Discussionsupporting
confidence: 90%
“…In consistent with our results on cancer prognosis, a prospective cohort study including 30 179 male and 26 005 female participants who were followed up for 9 years presented that low serum cholesterol was associated with increased risk for overall cancer mortality (HR = 1.52; 95% CI: 1.06–2.18) . Previous epidemiological studies also provided that decreased level of HDL‐C could be an easily measured predictor for inferior prognosis in breast, prostate cancer and non‐small cell lung carcinoma . Wang et al .…”
Section: Discussionsupporting
confidence: 90%
“…After a series of screening based on the inclusion/exclusion criteria mentioned above, 8 publications were eventually eligible for the meta-analysis. [26,29,[33][34][35][36][37][38] All these studies were published in peer-reviewed journals.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Some studies reported that the high expression of serum CRP was correlated with unfavorable prognosis, [26,27] while some others did not show any significant link between CRP and NSCLC survival. [28,29] In this study, we performed an updated meta-analysis to give a comprehensive evaluation on the prognostic role of CRP in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [11][12][13] have reported a significant inverse relation between HDL and disease prognosis at many sites. As shown in a study by Chi et al [11]., high HDL was an independent prognostic factor of PFS in lung adenocarcinoma patients. Another study by Wolfe et al [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a significant inverse relation between lipoproteins and the risk of cancer at multiple sites [8][9][10]. Furthermore, recent studies have demonstrated that HDL was a favorable prognostic marker in several cancers, including cancers of the lung, breast and stomach [11][12][13][14]. Studies have also suggested that LDL enhances the colorectal cancer progression via reactive oxygen species (ROS) and the mitogen-activated protein kinase (MAPK) pathway [13].…”
Section: Introductionmentioning
confidence: 99%